PENGARUH LINGKUNGAN KERJA, KOMPENSASI PELENGKAP, DAN PERKEMBANGAN KARIR TERHADAP LOYALITAS KARYAWAN DI PT INDOLAKTO - Roni Hermanto; Darlius (Pasca Sarjana Universitas Satya Negara Indonesia, 2016)
This research was conducted to analyze the effect of the work environment, fringe benefit, and career development to employee loyalty at PT Indolakto. Samples used in this research were 100 employees at the level of supervisors and managers. Collecting data using questionnaires were analyzed using path analysis. Results of the analysis showed that the work environment directly influence employee loyalty with total direct effect and indirect effect amounted to 37,24%, work environment directly influence career development amounted to 38.62%, fringe benefit directly influence employee loyalty with total direct effect and indirect effect amounted to 26.13%, the fringe benefit had an indirect effect on career development for 6,14%, career developmnet directly influence employee loyalty with total direct effect and indirect effect amounted to 39.42%. In order to increase the loyalty of employees at PT Indolakto, things that can be done such as care about physical environment and non-physical environment, give fringe benefit or allowances according to the needs of employees, and then making plans regarding career development of employees and given the opportunity for more advanced.